Built environment influences on healthy eating and active living: The NEWPATH study. Issue 2 (26th January 2022) - Frank, Lawrence D.; Bigazzi, Alexander; Hong, Andy; Minaker, Leia; Fisher, Pat; Raine, Kim D.
Abstract: Objective: The Neighbourhood Environments in Waterloo: Patterns of Active Transportation and Health (NEWPATH) study examined built environment influences on travel, physical activity, food consumption, and health. This collaboration between researchers and practitioners in health and transportation planning is the first, to our knowledge, to integrate food purchasing, diet, travel, and objectively measured physical activity into a trip‐destination protocol. This study simultaneously examines diet and physical activity relationships with BMI and waist circumference (WC). Methods: Individual diet and travel diary data were linked to objective built‐environment measures of walkability and retail food environments. BMI and WC were self‐reported ( n = 1, 160). Some respondents wore accelerometers to objectively measure physical activity ( n = 549). Pathways from the built environment through behavior (walking and eating) to BMI and WC were assessed using path analysis. Results: Walkability was associated with lower BMI and WC through physical activity and active travel. Healthy retail food environments were associated with healthy eating and lower BMI and WC, whereas walkability and healthy retail food environments were insignificant ( p < 0.05). Walkable neighborhoods had less healthy food environments, but active travel was not associated with healthy eating or caloric intake. Conclusions: Findings highlight the importance of neighborhood walkability and food environments in shaping physical activity, diet, and obesity.